Peningkatan gizi anak melalui inovasi pembuatan susu jagung sebagai upaya mengatasi stunting di Desa Belung - Riyandini, Ariyanti Septy; Hidayat, Muhammad Rizal; Putri, Aisyah Diah Ayu; Salsabila, Nurul Yulaicha Salma; Mu’is, Ahmad (Maliki Interdisciplinary Journal, 2024)
One of the global nutritional problems, especially in developing and poor countries, is stunting. Stunting is a concern because it is associated with a higher risk of morbidity and death, as well as inadequate brain development, which hinders the development of motor skills and inhibits brain growth. The method used in this activity is an in-depth observation stage of the condition of stunting in the community, including analysis of the nutrition and diet of people who have the potential to experience stunting as well as through the socialization stage carried out regarding the training program for the people of Belung Milk Corn Anti-Stunting Village which has The nutritional value in the form of protein plays a crucial role in preventing stunting because it is the basic ingredient for the growth and development of body cells. Talking about stunting prevention, it is important to emphasize the need to consume adequate and high-quality protein intake to ensure children receive the nutrition they need for healthy growth and development. One of the food problems faced by people throughout the world, especially in developing and poor countries like Indonesia, is stunting. As a way to prevent this problem, dairy products are made whose main ingredients are corn and a combination of soy milk. Protein is thought to be abundant in these products, and protein is essential for a child's growth and development. This product, with its high nutritional content, is expected to replace unhealthy drinks in the diet and reduce stunting.